MEASUREMENT OF ELECTRIC ENERGY CONSUMPTION: ALGORITHM FOR DETECTING POTENTIAL USERS OF THERMO-ACCUMULATION AS AN ALTERNATIVE FOR LOAD SHIFT - PATRÍCIA VALÉRIA SATHLER DE QUEIROZ (2011)
PONTIFÍCIA UNIVERSIDADE CATÓLICA DO RIO DE JANEIRO